2003
DOI: 10.1046/j.1526-0968.2003.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Immune Imbalance: The Use of Prosorba Column Treatment for Immune Disorders

Abstract: The treatment of selected refractory autoimmune diseases has been complemented by the use of Protein A (Prosorba column) immunoadsorption. US Food and Drug Administration-approved clinical applications include idiopathic thrombocytopenia purpura (ITP) and rheumatoid arthritis (RA). Other common off label uses include thrombotic thrombocytopenic purpura (TTP) and hemolytic uremic syndrome (HUS). Less common experimental uses in diseases in which efficacy has been reported include autoimmune CNS syndromes, perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Treatment of peripheral blood lymphocytes with SA-FasL under extracorporeal conditions (ex vivo) from newly diagnosed patients in the honeymoon period with a considerable pancreatic islet mass and return of these cells into the patients may provide a novel means of immune intervention. A similar approach, where highly purified, protein-A bound to a silica matrix known as Prosorba columns is used to remove autoantibodies and immune complexes from the blood of rheumatoid arthritis patients, has already been tested in multiple clinical trials with reported efficacy (Felson et al, 1999;Levy and Degani, 2003). Inasmuch as SA-FasL can easily be attached to biotinylated beads, the application to IDDM or other autoimmune diseases with T cell etiology are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of peripheral blood lymphocytes with SA-FasL under extracorporeal conditions (ex vivo) from newly diagnosed patients in the honeymoon period with a considerable pancreatic islet mass and return of these cells into the patients may provide a novel means of immune intervention. A similar approach, where highly purified, protein-A bound to a silica matrix known as Prosorba columns is used to remove autoantibodies and immune complexes from the blood of rheumatoid arthritis patients, has already been tested in multiple clinical trials with reported efficacy (Felson et al, 1999;Levy and Degani, 2003). Inasmuch as SA-FasL can easily be attached to biotinylated beads, the application to IDDM or other autoimmune diseases with T cell etiology are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these findings support evidence that immunosuppressive drugs should be considered in patients with detectable inhibitory anti‐ADAMTS13 antibodies, in an attempt to enhance treatment responsiveness and to prevent episodes of flare‐up. The possible usefulness of other apheresis techniques, such as immunoadsorption columns, should also be evaluated in these patients (Levy & Degani, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the Prosorba ® treatment has shown unique characteristics and clinical results, which made it desirable at least for refractory patients. The implementation of treatment, however, was limited by the observed successful outcome in only approximately 40% of treated patients 51. As in this number the amount of side effects on the outcome percentage is not specifiable, one may speculate that with less side effects the successful outcome may even be greater.…”
Section: Discussionmentioning
confidence: 96%